FAKTOR KEJADIAN ASFIKSIA NEONATORUM - Mentari Mentari; Rachmawati Rachmawati; Elvi Destariani (JURNAL PENELITIAN TERAPAN KESEHATAN, 2020)
Abstract: Asphyxia is a condition of newborns who fail to breathe spontaneously and regularly soon after birth that also affect the high infant mortality rate. Data Rejang Lebong on neonatal mortality in 2015 was 42 cases the cause of death by asphyxia neonatorum in the second amounted to 9 babies. The purpose of this research is knowing the factors that led to the incident Neonatorum asphyxia in newborns in hospitals Curup 2016.The research with case control approach with secondary data of 228 samples of baby ie 76 samples 152 samples of case group and the control group. Data analysis techniques with Chi-Square test and Multiple Logistic Regression Analysis.Chi-Square test results obtained p = 0.020 for maternal age, p = 0.013 for parity, p = 0,000 for gestational age, p = 0.013 for labor type, and p = 0,000 for low birth weight. Logistic regression analysis obtained two dominant factors influencing the incidence of asphyxia neonatorum that is Low Birth Weight with Odds value The biggest ratio (3,828) and gestational age with Odds Ratio (3,628). The results prove that risk factors such as maternal factors, infant factors and factors of labor is a factor that can cause neonatal asphyxia.Keywords: Age, parity, gestational age, type of delivery, low birth weight, neonatal asphyxia